Guidance Note for the Liberalization and Management of Capital Flows. (Policy Papers; Policy Paper ;, 2013)
This note provides operational guidance to staff for how to use the Fund's institutional view on the liberalization and management of capital flows. The institutional view is a consistent basis for providing policy advice on capital flows and policies related to them and assessments when required for surveillance. In the absence of an institutional view, country teams risk providing inconsistent advice to countries in similar circumstances (IEO, 2005). The view does not have mandatory implications for Fund-supported programs or technical assistance. It does not alter members' rights and obligations under the Fund's Articles of Agreement or under any other international agreements. The institutional view and guidance will evolve over time to reflect new experience, emerging views of authorities and staff, and research. Staff teams are encouraged to reflect useful lessons from authorities' experiences with capital flow liberalization and management in Fund reports so that these experiences can continue to influence the Fund's approach to these issues.